Detection of Enteropathogenic Bacteria under Fingernails of Canteen Workers at Universitas Padjadjaran, Jatinangor - Nahenthran, Nalinie Nalammah; Megantara, Imam; Raksanagara, Ardini S (Althea Medical Journal, 2016)
Background: Food poisoning is a major problem in Indonesia as most people do not clean under their fingernails to remove bacteria. This study was designed to detect enteropathogenic bacteria under the fingernails of canteen workers in Universitas Padjadjaran, Jatinangor.Methods: A cross-sectional study was conducted from OctoberâNovember 2014 at the Faculty of Medicineâs Microbiology Laboratory to detect enteropathogenic bacteria under the fingernails of canteen workers in Universitas Padjadjaran, Jatinangor. Based on the inclusion and exclusion criteria of the study, 30 canteen workers were selected by random sampling from three canteens. Samples were collected from the fingernails of both the right and left hands by using a cotton swab. Sixty specimens were cultured for identification of the enteropathogenic bacteria by using gram staining method and biochemical tests.Results: The highest percentage of enteropathogenic bacteria found under the fingernails of canteen workers was Klebsiella pneumoniae with a percentage of 45% followed by Enterobacter aerogenes with a percentage of 25.7%, Salmonella paratyphii with a percentage of 9.7%, E. coli with a percentage of 6.4%, and Serratia sp, Proteus mirabillis, Klebsiella oxytoca and Shigella sp. with a percentage of 3.2%.Conclusions: The highest number of bacteria found under the fingernails of the canteen workers is Klebsiella pneumoniae, followed by Enterobacter aerogenes, Salmonella paratyphii and E. coli which has potential to cause gastroenteritis if cross-contamination occurs between the fingernails and the food.[AMJ.2016;3(2):309â13]DOI:Â 10.15850/amj.v3n2.798Â